IDENTIFICATION OF PCI GIRDER BRIDGE STRUCTURE RESPONSE PATTERNS BASED ON DAMAGE LOCATION IN LONGITUDINAL DIRECTION USING MIDAS CIVIL 2019 FINITE ELEMENT ANALYSIS - Hutomo, Priyo
Indonesia's diverse topographic conditions, consisting of many rivers, swamps, and mountains, make the existence of bridges indispensable and familiar in people's daily lives. Bridges like other civil structures will also experience a decrease in quality or deterioration caused by many factors, including overload during operation, the effect of age on materials, and environmental effects. Efforts to maintain the condition of the bridge structure from deteriorating conditions have so far been carried out by periodic visual inspections, but there are shortcomings in the form of a limited inspection schedule only a few times within a certain period time causing the possibility that damage that occurs escapes the bridge inspection schedule. Therefore, a structural health monitoring system is needed that can reduce the level of subjectivity of the examiner and can reduce the difficulty of obtaining accurate results due to the geometric shape of the bridge, and can monitor the condition of the bridge continuously and automatically by installing sensors on the bridge. Before the sensor application is installed on the bridge, reference data is needed as a guide for determining the condition of a bridge in the form of a data bank that summarizes all conditions that may occur on a bridge, with various scenarios of variations in the condition of the bridge. And this study aims to provide the data bank with Finite Element Analysis (FEA) modeling using the MIDAS CIVIL 2019 application with a research focus on damage detection and damage localization (longitudinal direction). The response data of the bridge structure used in this study are Frequency Response for detection of damage and Deflection to determine the location of the damage. The bridge object used in this research is PCI Girder with a span of 40.00 m.